Rate‐limiting step analysis of the microbial desulfurization of dibenzothiophene in a model oil system. Issue 5 (27th November 2013) - Abin‐Fuentes, Andres; Leung, James C.; Mohamed, Magdy El‐Said; Wang, Daniel I.C.; Prather, Kristala L.J.
ABSTRACT A mechanistic analysis of the various mass transport and kinetic steps in the microbial desulfurization of dibenzothiophene (DBT) by Rhodococcus erythropolis IGTS8 in a model biphasic (oil–water), small‐scale system was performed. The biocatalyst was distributed into three populations, free cells in the aqueous phase, cell aggregates and oil–adhered cells, and the fraction of cells in each population was measured. The power input per volume (P/V) and the impeller tip speed (vtip) were identified as key operating parameters in determining whether the system is mass transport controlled or kinetically controlled. Oil–water DBT mass transport was found to not be limiting under the conditions tested. Experimental results at both the 100 mL and 4 L (bioreactor) scales suggest that agitation leading to P/V greater than 10, 000 W/ m3 and/or vtip greater than 0.67 m/s is sufficient to overcome the major mass transport limitation in the system, which was the diffusion of DBT within the biocatalyst aggregates. Biotechnol. Biotechnol. Bioeng. 2014;111: 876–884. © 2013 Wiley Periodicals, Inc.